2022
DOI: 10.3390/ijerph19095029
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi and Glomalin Play a Crucial Role in Soil Aggregate Stability in Pb-Contaminated Soil

Abstract: With the rapid development of industrialization and urbanization, soil contamination with heavy metal (HM) has gradually become a global environmental problem. Lead (Pb) is one of the most abundant toxic metals in soil and high concentrations of Pb can inhibit plant growth, harm human health, and damage soil properties, including quality and stability. Arbuscular mycorrhizal fungi (AMF) are a type of obligate symbiotic soil microorganism forming symbiotic associations with most terrestrial plants, which play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Therefore, changes in GRSP in the aggregate fraction may have a direct impact on aggregate stability. The results of this study showed that both EE-GRSP and T-GRSP were positively correlated MWD and GMD ( Supplementary Figure 5 ), which was consistent with most previous studies ( Wu et al, 2012 ; Li et al, 2022 ). However, the effect of GRSP on soil aggregate stability was greatly linked to the soil particle size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, changes in GRSP in the aggregate fraction may have a direct impact on aggregate stability. The results of this study showed that both EE-GRSP and T-GRSP were positively correlated MWD and GMD ( Supplementary Figure 5 ), which was consistent with most previous studies ( Wu et al, 2012 ; Li et al, 2022 ). However, the effect of GRSP on soil aggregate stability was greatly linked to the soil particle size.…”
Section: Discussionsupporting
confidence: 92%
“…Our research indicates that CC and LUC could regulate GRSP and soil aggregate stability mainly by regulating AMF diversity, network complexity, and growth parameters based on the results of random forest model ( Supplementary Figure 4 ). Importantly, GRSP was located in the core position to influence the stability of soil aggregates and was the most important factor for explaining soil aggregation ( Li et al, 2022 ). Therefore, changes in GRSP in the aggregate fraction may have a direct impact on aggregate stability.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the results of soil protein (glomalin), concentration and biomass, can understand the direct correlation between them. Also, there are some similar reports to approve this (YANG et al, 2017;LI et al, 2022).…”
Section: Glomalin Concentrationmentioning
confidence: 76%
“…Microbial necromass C (Liang et al 2020) or microbial residues (Joergensen and Wichern 2018) embraces all freshly synthesized microbial non-biomass metabolites that leave the cells, such as exo-enzymes (Burns et al 2013), extracellular polymeric substances (Redmile-Gordon et al 2014), e.g. the glomalin-related soil protein (Wright and Upadhyaya 1996;Spohn and Giani 2011;Li et al 2022), other secondary metabolites, e.g. antibiotics (Boruta 2018;Keller 2019), and dead tissue remains (Joergensen and Wichern 2018).…”
Section: Cue Calculationsmentioning
confidence: 99%